Social networks and condomless intercourse with female partners among male sex workers in the Dominican Republic - Saiyed, Faiez K. (2021)
Male sex workers (MSW) in the Dominican Republic (DR) have multiple sexual partners, including personal and client-relationships, and are disproportionately affected by human immunodeficiency virus (HIV). We examined the prevalence of condomless anal and/or vaginal intercourse (CI) among MSW in the DR as a function of social network factors. Self-report surveys and social network interviews were administered to MSW recruited through venue-based sampling (N = 220). A generalized linear model was used to complete a Poisson Regression model and identify variables significantly associated with the outcome of interest. CI was more common with female (28.3%) than with male partners (4.9%). Factors associated with CI with the last female partner included older age of MSW, CI with the last male partner, having a stable female partner (a consistent or main partner), and having ≥1 family member in the participants’ social network. Partner and social network characteristics associated with CI among MSW suggest the utility of dyadic and network interventions to reduce HIV risk.